Osteoclast-type giant cell tumour of the pancreas. Issue 10 (October 1983) - Jeffrey, I; Crow, J; Ellis, B W
Abstract : A case of osteoclast-type giant cell tumour of the pancreas is described and the features of eight other previously reported patients are reviewed. Characteristically, these neoplasms are large at presentation and show focal haemorrhage and necrosis, but seem slow to give rise to metastases. Histological examination reveals numerous osteoclast-like giant cells set in a sarcomatous stroma, the appearances being similar to those seen in giant cell tumours of bone. They are distinct from pleomorphic giant cell carcinomas of the pancreas and may have a slightly better prognosis after resection than ordinary adenocarcinomas. The histogenesis of these rare tumours is unknown.